Study on temperature characteristics of multi-tower cable-stayed bridge - Liu Chengyuan; Han Zhuowei; Li Wei; Zhao Lin (Archives of Civil Engineering, 2023)
Temperature effects have a great influence on the mechanical behavior of cable-stayed bridges, especially for long-span bridges, which have significant time-varying and spatial effects. In this paper, the temperature characteristics of multi-tower cable-stayed bridge are obtained by data acquisition with wireless acquisition module. The test results show that: the daily temperature-time curves of atmospheric temperature and structural temperature are similar to sinewaves with obvious peaks and troughs; structure temperature and atmospheric temperature have obvious hysteresis; longitudinal displacement, transverse displacement and vertical of mid-span beam are negatively correlated with atmospheric temperature; the temperature distribution of the cable tower is not uniform, and the maximum temperature difference of the section is 23.7°C considering 98% of the upper limit value; the longitudinal, transverse and vertical displacement of cable tower and the cable force is negatively correlated with atmospheric temperature, and the relationship between cable force and atmospheric temperature is a cubic function rather than linear function.